Value of PASI90 Versus Merit-Based Incentive Payment System Efficacy Measures. Issue 3 (July 2022) - Hawkes, Jason E.; Reis, Paulo; Lin, Chen-Yen; Muram, Talia; Eastman, William J.
Background: Achieving ≥90% improvement in Psoriasis Area and Severity Index (PASI90) is achievable with newer biologic therapies, such as ixekizumab. Standard of care payment systems such as the Merit-based Incentive Payment System (MIPS) responder criteria could lead to under treatment and lower quality of life (QoL) outcomes compared with PASI90. Objective: Show PASI90 is a higher standard than MIPS and is associated with greater improvements in QoL and other PRO outcomes. Methods: Patients with moderate-to-severe psoriasis meeting PASI90 and MIPS criteria were compared in 3 phase 3 clinical trials of the interleukin-17A inhibitor ixekizumab (pooled UNCOVER-2/3 and IXORA-S). Patients satisfying MIPS criteria met either static Physician Global Assessment score ≤2, body surface area <3%, PASI <3, or Dermatology Life Quality Index ≤5. Improvements in QoL were compared between patients meeting PASI90 and MIPS criteria. Results: All PASI90 responders were also MIPS responders (PASI90 responders). Not all MIPS responders met PASI90 (MIPS-only responders). Significantly larger change from baseline improvements for all health (skin pain, Itch NRS, DLQI, PtGA, WPAI-PsO work productivity loss, and WPAI-PsO activity impairment) and quality of life (EQ-5D 5L VAS and acute SF-36 PCS/MCS) outcome measures were observed in the PASI90 responders vs the MIPS-only responders. Conclusion: PASI90 is a higher standard of response than MIPS and is associated with greater improvements in health and quality of life outcome measures.